Coupling online control and inhibitory systems in children with Developmental Coordination Disorder: Goal-directed reaching. (January 2015) - Ruddock, Scott; Piek, Jan; Sugden, David; Morris, Sue; Hyde, Christian; Caeyenberghs, Karen; Wilson, Peter
Highlights: Separate lines of work have shown that online control and executive function (e.g., inhibition) are compromised in children with DCD. The study reported here shows that superimposing an inhibitory constraint on a modified rapid reaching task exacerbates deficits in online control among children with DCD; however, this deficit appears to dissipate with age. Longitudinal data is needed to clarify the nature of the coupling between frontal executive and motor control systems. The interaction between motor control and executive function should be considered when planning interventions for DCD. Abstract: For children with Developmental Coordination Disorder (DCD), the real-time coupling between frontal executive function and online motor control has not been explored despite reported deficits in each domain. The aim of the present study was to investigate how children with DCD enlist online control under task constraints that compel the need for inhibitory control. A total of 129 school children were sampled from mainstream primary schools. Forty-two children who met research criteria for DCD were compared with 87 typically developing controls on a modified double-jump reaching task. Children within each skill group were divided into three age bands: younger (6–7 years), mid-aged (8–9), and older (10–12). Online control was compared between groups as a function of trial type (non-jump, jump, anti-jump). Overall, results showed that while movement times were similar between skill groups under simple task constraints (non-jump), on perturbation (or jump) trials the DCD group were significantly slower than controls and corrected trajectories later. Critically, the DCD group was further disadvantaged by anti-jump trials where inhibitory control was required; however, this effect reduced with age. While coupling online control and executive systems is not well developed in younger and mid-aged children, there is evidence of age-appropriate coupling in older children. Longitudinal data are needed to clarify this intriguing finding. The theoretical and applied implications of these results are discussed.